2020
DOI: 10.1007/s11894-019-0740-3
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics, Nutrition, and the Small Intestine

Abstract: Purpose of Review Probiotics are promising remedial treatments for symptoms of small intestine (SI) diseases and promoters of overall good health. Probiotics play an important role in supporting a healthy SI microbiome (eubiosis), and in preventing establishment of unhealthy microbiota. SI eubiosis promotes optimal nutrient uptake, and optimal nutritional status maintains a healthy SI, reducing the likelihood of SI diseases. It is important to understand the advantages and limitations of probiotic therapies. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(66 citation statements)
references
References 75 publications
0
63
0
3
Order By: Relevance
“…An important characteristic for LAB to be considered as probiotics is its ability to resist bile salts in the small and large intestines [ 30 ]. The results of this study indicated that the identified LAB can survive in small and large intestines.…”
Section: Resultsmentioning
confidence: 99%
“…An important characteristic for LAB to be considered as probiotics is its ability to resist bile salts in the small and large intestines [ 30 ]. The results of this study indicated that the identified LAB can survive in small and large intestines.…”
Section: Resultsmentioning
confidence: 99%
“…Of particular interest, L. brevis MYSN105 was highly potent against F. verticillioides while exhibiting attractive probiotic attributes. Taroub et al (2019) and Judkins et al (2020) showed that LABs are found in diverse ecological niches, including fermented food products, where they play an important role in nutrition and maintaining gut health. They are also promising biological control agents reported in several studies for their antifungal activity while being generally regarded as safe (GRAS).…”
Section: Discussionmentioning
confidence: 99%
“…It was largely depended on intestinal microbial disorders and increased intestinal permeability. 21,22 According to our data, despite of the rehabilitation of Lactobacillus, the balance of intestinal microbiota of SHRs after valsartan administration was not powerful enough. So, we further focused on the intestinal mucosal barrier.…”
Section: Resultsmentioning
confidence: 80%